TINGKAT PENGETAHUAN MASYARAKAT TERHADAP PENANGANAN AWAL SENGATAN UBUR-UBUR DI DESA LUHU KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Wakano, Ferros Rozik; Hataul, Is Ikhsan; Manuputty, Amanda Grace (PAMERI, 2024)
Jellyfish are one of the dangerous sea animals and often attack humans through their stings. Jellyfish contain toxins in the form of cardiotoxins, neurotoxins, and myotoxins which when exposed to humans can cause shock and even death. The purpose of this study was to determine the level of knowledge of the community in Luhu Village regarding the initial handling of jellyfish stings. This study is a descriptive quantitative study using a cross sectional design with a community sample of 200 samples. Data collection using questionnaires. The questionnaire data is then processed and analyzed using the SPSS program. The results of the research based on the characteristics of respondents, the most respondents found in this study were female as many as 118 respondents (59%), the age of respondents was adult age as many as 114 respondents (57%), many respondents' occupations were farmers namely 64 respondents (32%), while the level of education that was found was high school which was 113 respondents (52%). Of the 200 respondents, 47 respondents (23.5%) had less knowledge, 133 respondents (56.5%) had sufficient knowledge, and 40 respondents (20%) had good knowledge. Knowledge is very influential on how to handle jellyfish stings early. Therefore, there is a need for socialization and counseling efforts as well as training by health workers to the community in order to increase the level of public knowledge about early handling of jellyfish stings.